Simple and Practical Method for Preparation of [(Diacetoxy)iodo]arenes with Iodoarenes and m-Chloroperoxybenzoic Acid - Iinuma, Masataka; Moriyama, Katsuhiko; Togo, Hideo (Synlett, 2012)
Various [(diacetoxy)iodo]arenes bearing 4-methylphenyl, phenyl, 4-nitrophenyl, 3-nitrophenyl, 4-cyanophenyl, 4-bromophenyl, 4-methoxycarbonyphenyl, 3,5-bis(trifluoromethyl)phenyl, and 4-(N,N,N-trimethylammonium)methylphenyl groups were efficiently prepared by the treatment of iodoarenes with m-chloroperoxybenzoic acid in acetic acid. The great advantage of the present method is the easy preparation and isolation of [(diacetoxy)-iodo]arenes bearing electron-withdrawing groups, such as 4-nitro, 4-cyano, 4-methoxycarbonyl, and 3,5-bis(trifluoromethyl) groups, on the aromatic ring.
Keywords: [(diacetoxy)iodo]arene; m-chloroperoxybenzoic acid; iodoarene; oxidation; acetic acid; electron-deficient aromatic ring